The Feasibility of Comic Media on Narrative Texts Based on Local Wisdom in VII Grade Student of Junior High School (SMPN) 3 Kotapinang - Asri Yulianda; Biner Ambarita; Khairil Ansari (BIRCU, 2019)
The aims of this study is to find out the feasibility of comic media on narrative texts based on local wisdom. The research was conducted in the second semester 2018/2019. The subjects in this study were students of VII grade of Junior High School (SMPN) 1 Kotapinang. The results of the material expert validation on the feasibility of material aspects gained an average of 89.37% with the category